5(x+y)=zforx

Simple and best practice solution for 5(x+y)=zforx equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(x+y)=zforx equation:


Simplifying
5(x + y) = zforx
(x * 5 + y * 5) = zforx
(5x + 5y) = zforx

Solving
5x + 5y = forxz

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1forxz' to each side of the equation.
5x + -1forxz + 5y = forxz + -1forxz

Reorder the terms:
-1forxz + 5x + 5y = forxz + -1forxz

Combine like terms: forxz + -1forxz = 0
-1forxz + 5x + 5y = 0

Add '-5y' to each side of the equation.
-1forxz + 5x + 5y + -5y = 0 + -5y

Combine like terms: 5y + -5y = 0
-1forxz + 5x + 0 = 0 + -5y
-1forxz + 5x = 0 + -5y
Remove the zero:
-1forxz + 5x = -5y

Combine like terms: -5y + 5y = 0
-1forxz + 5x + 5y = 0

The solution to this equation could not be determined.

See similar equations:

| 9-c=12-5c | | f(x)=x^2-10x+98 | | 5x^2+26-24=0 | | Y=8/9x-4 | | 9x-1=107 | | x^3+3x-2=0 | | 7[4-(3-5x)]+x=4(9x+2)-1 | | -10x+3(x-4)+6x=5x-48 | | 2-6=36x-5 | | x-2+x+3=3x-4 | | x(5x+7)=2x^2-9x+64 | | 15x-60=-12x-54 | | -[4z-(9z+8)]=8+(4z+6) | | 3x^9/2x^5 | | 10+6r=104 | | 8a-2a+12=10a-4 | | 10-6r=104 | | 10a-22=13a+5 | | 15=6-2a | | 7+1=7x-11 | | 4a+18=2a-26 | | 1=(x+1)ln(x+1)+xln(x) | | 2x-3=10x+19 | | 3D+2W=18 | | y+1(9+24)-21=21 | | 3xy-2x+4= | | 12a/8/5 | | 6x+2=2x+18 | | 5g+7g=10g | | 2a+b=210 | | (10)(9.8)sin(30)= | | (5x-3y)(x^6-4xy+2y^2)= |

Equations solver categories